Preventable morbidities of a successful intervention, Textiloma/Gossypiboma: a case series - Anwar Zeb Khan,; Fatima, Tausief; Urwah Kafeel,; Muhammad Farooq Afzal,; Suleman Asif,; Ahsan Rasheed Ghumman, (Journal of the Pakistan Medical Association, 2023)
Preventable morbidities are serious conditions that has the potential to cause serious harm or death of the patient. One of the preventable morbidities is Gossypiboma or involuntary leaving of surgical sponge inside the body. The implication for the patient and the surgeon is grave. Gossypiboma is preventable if guidance and safety recommendations are followed. The purpose of presenting this case series is to rekindle awareness of the phenomena of Gossypiboma, highlight the implications, and stress prevention. Data of patients presented in the Lahore General Hospital was collected, which includes their demographic, clinical features, and management outcome. Their age, gender, surgery conducted, onset of symptoms, and salvage procedure were noted. ---Continue